ADSORPSI ION LOGAM Cu(II) DAN Cr(VI) OLEH ASAM HUMAT HASIL ISOLASI DARI TINJA SAPI - , Ekacahyana Mandasari ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The adsorption of Cu(II) and Cr(VI) on humic acid (HA) has been conducted. The goals of this research were to analyze HA isolation pathway from cow dung. The parameter of this research are effect of medium acidity, kinetic and isotherm adsorption. The isolation process was done by alkali extraction method. The optimum pH of Cu(II) ion adsorption was achieved pH 4 while Cr(VI) ion at pH 1. The adsorption rates of Cu(II) and Cr(VI) ions on humic acid were 0.92 and 0.36 g/mmol.minute, respectively. Based on Hoâs equation showed that kinetic adsorption followed the pseudo second-orders. The adsorption capacities for Cu(II) and Cr(VI) were 0.147 and 0.235 mmol/g, respectively. Adsorption energies for Cu(II) and Cr(VI) were 18.28 and 21.91 kJ/mol, respectively. Key words: Humic acid, cows dung, adsorption, Cu(II) metal ion, Cr(VI) metal ion